The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1007/bf02381138
|View full text |Cite
|
Sign up to set email alerts
|

The extensor and peroneal muscles of the crab-eating monkey (Macaca fascicularis)

Abstract: ABSTRACT. On the basis of 60 hindlimbs of 30 crab-eating monkeys (Macacafascicularis) of each sex, the morphology of the crural extensor and the peroneal group of leg muscles is described and some functional indices are calculated. For the attachments and measurements of the muscles, the results obtained in this study generally agreed with those of other Macaca species. The crural extensor has minor differences. Some anomalous modes of insertion are observed in the peroneal group. These results indicate the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on the relative abundance of medial accessory tendons to lateral accessory tendons (or muscle–tendon units), Kaneff and Stephanoff (1982:699) suggested that medial reorganization of the extensor muscles may be ‘phylogenetically older’ than lateral reorganization. Accessory hallucal extensor muscles are absent from the feet of non‐human primates (Kaneff & Stephanoff, 1982; Kimura et al ., 1988; Langdon, 1990), making this hypothesis difficult to test using phylogenetic methods. Although small tendinous slips may expand the insertion of EHL in some monkeys (see Kimura et al ., 1988 and references therein), accessory muscles and major tendons of the hallucal extensors seem to be unique to humans among primates.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the relative abundance of medial accessory tendons to lateral accessory tendons (or muscle–tendon units), Kaneff and Stephanoff (1982:699) suggested that medial reorganization of the extensor muscles may be ‘phylogenetically older’ than lateral reorganization. Accessory hallucal extensor muscles are absent from the feet of non‐human primates (Kaneff & Stephanoff, 1982; Kimura et al ., 1988; Langdon, 1990), making this hypothesis difficult to test using phylogenetic methods. Although small tendinous slips may expand the insertion of EHL in some monkeys (see Kimura et al ., 1988 and references therein), accessory muscles and major tendons of the hallucal extensors seem to be unique to humans among primates.…”
Section: Discussionmentioning
confidence: 99%